Use of historical data as a decision support tool in watershed management: a case study of the Upper Nilwala Basin in Sri Lanka - Elkaduwa, W.K.B.; Sakthivadivel, Ramaswamy (International Water Management Institute, 1999)
Watershed analysis provides a framework for ecosystem management, which is currently the best option for conservation and management of natural resources. The current methods of assessing hydrologic impacts of land use transformation at the watershed scale, particularly in the tropics, are impaired by technical, financial and time constraints. This study provides an alternative approach to ascertain the actual changes in hydrologic response of a particular watershed to land use transformations made in the past.